Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 213662 by Spillover last updated on 13/Nov/24

Answered by mathmax last updated on 14/Nov/24

I=∫_0 ^∞ (x^2 /(1+e^x ))dx ⇒I=∫_0 ^∞ ((e^(−x) x^2 )/(1+e^(−x) ))dx  =∫_0 ^∞ x^2 e^(−x) Σ_(n=0) ^∞ (−1)^n e^(−nx) dx  =Σ_(n=0) ^∞ (−1)^n ∫_0 ^∞ x^2 e^(−(n+1)x) dx   (n+1)x=t  =Σ_(n=0) ^∞ (−1)^n ∫_0 ^∞  (t^2 /((n+1)^2 ))e^(−t) (dt/(n+1))  =Σ_(n=0) ^∞ (((−1)^n )/((n+1)^3 ))∫_0 ^∞ t^(3−1) e^(−t) dt  =Γ(3).Σ_(n=0) ^∞ (((−1)^n )/((n+1)^3 ))  we have Σ_(n=0) ^∞ (((−1)^n )/((n+1)^3 ))=Σ_(n=1) ^∞ (((−1)^(n−1) )/n^3 )  =eta(3)=(1−2^(1−3) )ζ(3)=(1−(1/4))ζ(3)  =(3/4)ζ(3)     Γ(3)=2!=2 ⇒I=(3/2)ζ(3)

I=0x21+exdxI=0exx21+exdx=0x2exn=0(1)nenxdx=n=0(1)n0x2e(n+1)xdx(n+1)x=t=n=0(1)n0t2(n+1)2etdtn+1=n=0(1)n(n+1)30t31etdt=Γ(3).n=0(1)n(n+1)3wehaven=0(1)n(n+1)3=n=1(1)n1n3=eta(3)=(1213)ζ(3)=(114)ζ(3)=34ζ(3)Γ(3)=2!=2I=32ζ(3)

Commented by Spillover last updated on 16/Nov/24

great solution

greatsolution

Terms of Service

Privacy Policy

Contact: info@tinkutara.com